The matter of miracles : Neapolitan baroque architecture and sanctity - Hills, Helen (Rethinking art's histories, 2016)
A study of the links between holy relics in baroque Naples and the urban environment in which they functioned, which shows that the urban setting was produced through the activities that took place there, and not the other way around